2006
DOI: 10.1103/physrevlett.96.227602
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Softening of the Ferroelectric Mode in the Isotope-Exchanged Strontium Titanate ofSrTiO318Studied by Light Scattering

Abstract: The E u mode of the isotope-induced ferroelectric strontium titanate SrTi 18 O 3 shows a perfect softening at the ferroelectric phase transition temperature T c , where the frequency of the underdamped mode approaches completely to zero within the instrumental resolution. The spectra of the Raman inactive soft E u mode have been successfully observed owing to local symmetry breaking and by long-term accumulation of the spectral intensity with a high resolution technique. The mechanism of the phase transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 25 publications
(31 reference statements)
5
69
0
Order By: Relevance
“…24-32cm -1 [11], and the latter is consistent with 13 cm -1 [20]. Our theory supports the complete softening of the phonon mode observed in the Raman spectrum [20].…”
Section: Formulationsupporting
confidence: 87%
“…24-32cm -1 [11], and the latter is consistent with 13 cm -1 [20]. Our theory supports the complete softening of the phonon mode observed in the Raman spectrum [20].…”
Section: Formulationsupporting
confidence: 87%
“…We are particularly grateful to H. Chamati and to N.S. Tonchev for pointing us to an error in the numerical analysis of equation (41) in an earlier version of this paper. We also acknowledge financial support from the National Science Foundation nsf-dmr 0645461 (L.Palova), NSF-NIRT-ECS-0608842 (P. Chandra) and the Department of Energy, grant DE-FE02-00ER45790 (P. Coleman).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…As the temperature is lowered from 180 K, these modes shift to lower wavenumbers unlike the conventional phonons. This anomalous behavior could be related to a phase transition at the magnetic or electronic transition temperature, [15,16] a structural phase transition, [17] contraction of the lattice. [18] However, in MnWO 4 , the magnetic and electronic transition temperatures are well below 180 K. In addition to the phonon softening, we have observed that one phonon mode (mode 5) disappeared above 180 K. Therefore, the phonon softening in our sample could be related with microscopic structured change.…”
Section: Resultsmentioning
confidence: 99%